PELATIHAN DAN PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BUMDES DESA BENTENG GAJAH KECAMATAN TOMPOBULU KABUPATEN MAROS - Abd. Gaffar; Rafika Amalia; Suardi; Ahmad Fajrin; Abd. Khalik (Fakultas Ekonomi dan Bisnis, 2022)
BUMDes is a village economic institution/body with legal entity formed and owned by the village government, managed economically independently and professionally with capital entirely or mostly separated village assets. Benteng Gajah is a village located in Tompobulu District, Maros Regency, which is located in a lowland area where most of the residents' livelihoods are from farming or farming. The implementation method carried out is to provide education through training and assistance in the preparation of simple or manual financial reports aimed at BUMDes Managers and Benteng Gajah Village Officials, Tompo Bulu District, Maros Regency. This Training and Assistance Activity for Preparing Simple Financial Statements was held on February 6 to 8, 2021, which was attended by 20 participants. This activity is expected to be useful and helpful in facilitating the process of preparing financial reports and BUMDes develops according to its objectives for the welfare of the Benteng Gajah village community.